PENGARUH PENGGUNAAN MASKER BUAH ALPUKAT TERHADAP PERAWATAN KULIT WAJAH KERING - Fabitiary, Annisa Rizqa; Hayatunnufus, Hayatunnufus; Astuti, Murni (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This type of research is quasi experiment with randomized control group design pretest-posttest design that is to explain the effect of the use of avocado mask on dry facial skin care. The object of research is the residential complex community Pelindo Jondul Rawang which has dry skin. Sampling is used with purposive sampling technique conducted in volunteer amounted to 9 people. The type of data used in this study is primary data, data analysis techniques using Analysis of Variance (ANOVA), followed by Duncan test to see the significant difference in the results of variance analysis. Normality and Homogeneity Analysis data is used to test analysis requirements before hypothesis testing. The results showed that in the Control Group (X1) without the use of avocado mask there was no change in skin moisture level and skin brightness level. In the experimental group 1 (X2) with the use of avocado mask the changes in skin moisture level and the brightness of the skin as well as the experimental group 2 (X3) showed a significant change in skin moisture level and skin brightness level. There is a difference in the effect of dry facial care in women aged 30-35 years using an avocado mask on three different treatments for moisture indicator and skin brightness with Significance of 0.001 <0.050. Based on the results of research is recommended to perform facial skin care with avocado as a face skin dry skin mask in women aged 30-35 years with the best usage frequency 2 x a week.Keywords: Face Care, Dry Skin. Avocado Fruit Mask